2015
DOI: 10.1515/johh-2015-0022
|View full text |Cite
|
Sign up to set email alerts
|

Identification of prevailing storm runoff generation mechanisms in an intensively cultivated catchment

Abstract: Abstract:The fact that flash floods initiated in arable catchments are often accompanied by massive sediment and nutrient loads often leads to the assumption that surface runoff is the principle pathway by which runoff reaches watercourses. On the basis of an evaluation of several rainfall-runoff events in a representative agricultural catchment, we show that runoff from cultivated land may be generated in a way similar to that seen on forested slopes, where shallow subsurface runoff is the predominant pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…1). The Nučice catchment (49 • 57 49.230 N, 14 • 52 13.242 E) was established in 2011 with the main purpose to monitor and study the rainfall-runoff and soil erosion processes by water originating from intensive rainfall over cultivated fields (Zumr et al, 2015).…”
Section: Site Descriptionmentioning
confidence: 99%
See 3 more Smart Citations
“…1). The Nučice catchment (49 • 57 49.230 N, 14 • 52 13.242 E) was established in 2011 with the main purpose to monitor and study the rainfall-runoff and soil erosion processes by water originating from intensive rainfall over cultivated fields (Zumr et al, 2015).…”
Section: Site Descriptionmentioning
confidence: 99%
“…Summer storm-runoff events accompanied by an increase in the concentration of suspended solids in the runoff are characteristic events. The storms cause a short, steep wave with a concentration time of 50 to 240 min (Zumr et al, 2015).…”
Section: Site Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Climate change notably has the potential to influence flow activation in agricultural systems by affecting precipitation characteristics such as form, amount, duration, and intensity, as well as soil antecedent moisture and temperature status (Bosch, Evans, Scavia, & Allan, ). Past studies conducted in humid temperate regions have shown that tiles significantly limit the initiation of saturation excess OF (SOF) by removing water from the vadose zone and by suppressing water table rise to the surface (Deasy, Brazier, Heathwaite, & Hodgkinson, ; Zumr, Dostál, & Devátý, ). However, Hortonian (or infiltration excess) OF (HOF) can still be activated when rainfall intensity exceeds the infiltration capacity of soil.…”
Section: Introductionmentioning
confidence: 99%